Visualization study on spray and ignition characteristics of high proportion methanol / PODE blended fuel - Rongkang SUN; Lijiang WEI; Wei SONG; Xiuwei LU; Chen HUANG (Journal of Thermal Science and Technology, 2025)
With the increasingly stringent emission requirements for shipping, methanol is a promising alternative fuel. The effects of mixing ratio and ambient temperature on the spray and ignition characteristics of high proportion methanol / Polyoxymethylene dimethyl ethers (PODE) blended fuel were studied on the visual constant volume combustion bomb experimental platform. The maximum mixing ratio of methanol was 70 %. The spray penetration, spray cone angle and spray area of the blended fuel increase with the increase of methanol ratio. During the development of the blended, the spray penetration first increases and then decreases, and finally tend to be stable. The time for the spray penetration to reach its peak is negatively correlated with the ambient temperature. As the methanol blending ratio increases, the flame spontaneous luminescence intensity and flame area decrease, and the ignition delay period prolongs. The increase of ambient temperature can improve the combustion performance of the blended fuel, but the effect of the mixing ratio on the fuel ignition gradually weakens with the increase of ambient temperature. It is of great significance to study the spray and ignition characteristics of high proportion methanol / PODE blended fuel for the application of high proportion methanol fuel in marine diesel engines.